Cuidado ou educação? As práticas pedagógicas nas escolas do rio Tucumanduba - CUNHA, Leila Silva (2024)
The present work of course completion aims to analyze how care and education are given, through pedagogical practices and how the family relationship is present and indispensable in this process. In order to develop this research, we used the exploratory and descriptive research, which aims at the documental analysis of the proposed theme through references of authors who discuss the subject about school, family and early childhood education. The type of approach was qualitative and the technique was the semi-structured interview, applied to parents and teachers of two schools located in the region of the islands of the municipality of Abaetetuba. The research data were collected over a period of four months, taking into account the theoretical arguments necessary for the construction of this work. The school must be of quality. You need to know a lot about the child's development and how it learns to have a positive impact.